First-principles study of the adsorption of water on tri-s-triazine-based graphitic carbon nitride - Aspera, Susan Meñez (Animo Repository, 2010)
As an initial step towards understanding the mechanism behind photocatalysis in graphitic carbon nitride (g-C3N4), we present a first-principles density functional theory (DFT) study of H 2O molecular adsorption on the tri-s-triazine-based structure. The optimization of the system determined that the most stable configuration would be on top of the two-coordinated nitrogen atom in an orientation where one O-H bond is parallel to the surface and the other one is pointing to the surface. The adsorption energy at the most stable configuration was found to be 0.82 eV with a barrier energy of ∼0:02 eV. Partial density of states (PDOS) and charge density distribution analysis show that, primarily, the bonding occurs between the hydrogen atom of the water molecule and the two-coordinated nitrogen atom of g-C3N4. Results of this study would be useful not only to better understand the mechanism behind H2O molecule adsorption but also to give insight into the role of the catalyst in the photocatalytic process. © 2010 The Japan Society of Applied Physics.